Finally a Bride - McDonough, Vickie (Uhrichsville, OH : Barbour Pub., 2011)
"Jacqueline 'Jack' Davis is a reporter for the Lookout Ledger bent on discovering the truth and nabbing her story at any cost. When Noah Jeffers comes to Lookout as a temporary pastor, Jack suspects there may be something hidden beneath his shepherding ways. Soon, though, Jack begins to be attracted to the new pastor despite her initial hesitation. But as she uncovers the truth, will this story cost her too much? Will she reveal what she's uncovered or keep it hidden to protect newfound love? Carly Payton returns to Lookout after years in prison, hoping to rebuild her life there. But she soon discovers that new beginnings and second chances are not always easy to find. Garret Corbett is determined to marry--but not to a jailbird like Carly. When Carly is equally repelled by Garret's prank-playing ways, will the two see past their dislike and give each other--and love--a second look?"--P. [4] of cover.
Keywords: Secrecy -- Fiction; Redemption -- Fiction; Mail order brides -- Fiction; Texas -- Fiction; Christian fiction; Love stories; Historical fiction